EVALUASI PENGGUNAAN OBAT CETIRIZINE DAN LORATADIN SEBAGAI ANTIHISTAMIN DI APOTEK KUSUMA FARMA KUDUS - Supriyanto; Endra Pujiastuti (Universitas An Nuur, 2022)
Background: Allergies are immune system reactions that occur after exposure to certain allergens. Antihistamines are widely used for the treatment of a variety of conditions, including acute allergic reactions, allergic rhinitis, allergic conjunctivitis, allergic asthma, urticaria and atopic dermatitis. Examples of antihistamines that are widely used are cetirizine and loratadine. Purpose: This study aims to determine the percentage of use of cetirizine and loratadine and to determine whether there is a significant difference in the use of the two antihistamines. Method: The research conducted was non-experimental, descriptive analysis, and retrospective. The subjects in this study were all allergic patients who received cetirizine and loratadine drugs at the Kusuma Farma Pharmacy during January-July 2021. Then the analysis and calculation of the percentage of cetirizine and loratadine drugs and the T-Test test were carried out to test the differences in use between the two drugs. Results: This study found that the majority of patients using cetirizine and lortadi were male (50,87%). The most use of Cetirizin was in January 2021 as many as 80 tablets and the least in April 2021, while the most Loratadine use was in July 2021 as many as 47 tablets and the least was in March. From January to July 2021, the use of Cetirizin was 354 tablets (68.13%), while the use of Loratadine in January to July 2021 was 167 tablets (31.87%).Conclusion: From the results of the evaluation study of the use of antihistamines Cetirizine and Loratadine in allergic patients at the Kusuma Farma Kudus Pharmacy for the period January to July 2021, the percentage of use of Cetirizine (68.13%) and Loratadine (31.87%) drugs. Based on the results of statistical testing, the T-test showed that there was a significant difference between the results of using the antihistamine drug Cetirizin and Loratadine